Herpetofauna of parque estadual altamiro de moura pacheco: One of the last remnants of seasonal forest in the core region of the Brazilian cerrado - Ramalho, Werther Pereira; França, Daniella Pereira Fagundes [UNESP]; Guerra, Vinicius; Marciano, Rosy; Do Vale, Nilton Carlos; Silva, Hélder Lúcio Rodrigues (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2018)
Studies in remnants of semi-deciduous seasonal forest of the Cerrado are needed to fill sampling gaps and improve basic knowledge of biodiversity. This study presents data on the herpetofauna of Parque Estadual Altamiro de Moura Pacheco, one of the last protected areas of seasonal forest in the core region of the Brazilian Cerrado. Fourteen sites were sampled between March 2007 and April 2008 using pitfall traps and active searches. A total of 35 anuran species were recorded, most of which were found in hygrophilous environments near forest fragments, open areas and riparian or gallery forest. A total of 29 reptile species were recorded, most of which were found in semi-deciduous forest and riparian or gallery forest. Fourteen of the amphibians and five of the reptiles are endemic to the Cerrado. The richness of amphibians and reptiles found in Parque Estadual Altamiro de Moura Pacheco is regionally representative, with communities typical of forest environments.
Keywords: Amphibians; Mato Grosso de Goiás; Protected area; Reptiles; Semi-deciduous forest